Effect of Fungicide Concentration with Active Ingredient Pyraclostrobin 250 EC on Leaf Spot Disease and Phylloplane Fungal Diversity in Mustard Plants (Brassica juncea L.) - Aritonang, Awal Josua; Martosudiro, Mintarto (University of Brawijaya, 2024)
Mustard greens (Brassica juncea L.) are vegetables that are widely liked by the public because they have benefits for body health. Mustard greens have benefits because they contain carbohydrates, proteins, and fats, 220 mg Ca, 38 mg P, vitamin A 6.4 mg, vitamin B 0.09 mg, and vitamin C 102 mg. Leaf spot disease caused by Alternaria sp. is one of the causes of the decline in mustard greens. This study aims to determine the effect of fungicide with the active ingredient pyraclostrobin on leaf spot disease and phylloplan fungal diversity in mustard plants with different concentrations. The study was carried out by applying fungicides with 6 treatments and 4 replicates with concentrations of 0.350 ml/l, 0.375 ml/l, 0.400 ml/l, 0.425 ml/l, and 0.450 ml/l. The results showed that fungicide with the active ingredient pyraclostrobin affected leaf spot disease and phylloplane fungal diversity in mustard plants. The intensity of leaf spot disease and phylloplane fungal diversity in the control treatment was higher than that of the fungicide treatment.